قرآنی سیرت نگاری میں ’’معراج انسانیت‘‘ از غلام احمد پرویز کی علمی حیثیت کا تحقیقی جائزہ: Analytical Study and Status of “Me’raj-e-Insaniat” by Ghulam Ahmad Pervaiz in Quranic Biography Books - Muhammad Hassam ul deen (MEI, 2023)
Ghulam Ahmad Pervaiz has been incorporated in Ahl-e-Quran of the Sub-Continent. He is also recognized as a refuter of Hadith. He is well known for his peculiar school of thought and to be great critic of doctrines and stand point of vast majority of Muslims. He has written on diverse topic and presented his own perspective. He is included in the list of multi-compilation erudite. His book on the biography of the Holy Prophet PBUH “Me’raj-e-Insaniat” is based upon the Holy Quran. In this book, the author, keeping in view the Holy Quran, tried to present the biography of Holy Prophet PBUH. By declaring the anthology of Hadith as doubtful, affirming the biographical book of the Holy Prophet PBUH as fabricated myths and designated the Quranic exegesis as unauthentic, he has asserted his own perspective. This book invites the erudite for more research.